Dual-Polarization, Tunable Breaking Window in the Polarization Conversion Pass Band in a Terahertz Dirac Semimetal-Based Metamaterial - Jianxing Zhao; Jianlin Song; Yao Zhou; Ruilong Zhao; Jianhong Zhou (IEEE Photonics Journal, 2019)
We propose a planar THz hybrid bulk Dirac semimetal (BDS)-metal metamaterial which consists of a hybrid BDS-metal array on a dielectric layer and a back metallic mirror. The simulation results show that a spectral window that possesses high reflectance with no polarization conversion effect arises in the polarization conversion pass band due to the existence of the BDS rods. Interestingly, though the proposed structure possesses no symmetry property, the effects are nearly the same for x- and y-polarization incidences. We analyze the electric field distributions at the breaking frequency and attribute the phenomena to plasmonic analogue of electromagnetically induced reflectance (EIR-like) effect for x-polarization incidence and direct back scattering for y-polarization incidence. The dependence of the breaking window on the BDS rod length shows that, for both x- and y-polarization incidences, the breaking characteristic is mainly determined by the dipole resonance on the BDS rod. Moreover, the breaking window can be independently and dynamically manipulated by changing the Fermi energy of the BDS rods. Our results may provide potential applications in designing new polarization control devices.